Allergic and environmental causes of asthma in children - Ayoub, Hanan Mohammed; Alali, Farah Abdulhameed; Kheyami, Fadilah Ali; Alsmeri, Reham Salem; Gazwani, Abdullah Salman; Abdulwahed, Razan Ahmed; Assiri, Amal Hassan; Alshaikhi, Maram Ibrahim; Najjar, Juwadaa Saleem Al; Ameen, Jasem Mohammad; Alkanderi, Roaa Ali (International Journal Of Community Medicine And Public Health, 2021)
Estimates show that asthma is highly prevalent across the different communities, and recent reports showed that by 2015, 300 million patients will be affected by asthma, and projections show that additional 100 million individuals will furtherly be affected by 2025. Many factors can attribute to the development of asthma, including genetic, environmental, and allergic causes. They have essential roles in the pathogenesis and development of the condition. Exposure to the different environmental factors has been an area of research for a long time to identify the potential factors that can cause sensitization and asthma development, especially among children that are more exposed to these factors because of their physical structure and daily outdoor activities. In the present literature review, we aim to provide a thorough discussion about the allergic and environmental causes of asthma in children. Our evidence indicates that exposure to different environmental factors including indoor and outdoor pollutants can significantly increase the risk of asthma. Furthermore, maternal exposure to certain pollutants in the prenatal period was also reported to be significantly associated with developing asthma in children around the age of 5 years old. Exposure to these substances increases the inflammatory and airway reactions leading to the development of asthma. Accordingly, healthcare authorities should plan for adequate interventions to reduce the exposure to these compounds among children and reduce the risk of developing asthma and respiratory tract morbidities.